Establishment and application of a TaqMan-based quantitative PCR assay for simultaneous detection of bovine Brucella spp. and Mycobacterium spp. - Zhang, Shuai; Zhao, Hui; Guo, Qiuju; Xue, Ruixue; Jiang, Zixin; Jiang, Wenduo; Xing, Linlin; Wei, Xinhui; Diao, Youxiang; Tang, Yi; Lan, Zouran; Zhang, Yue (Frontiers in Microbiology, 2025)
Brucellosis and tuberculosis are two zoonotic, chronic infectious diseases caused by bacteria of the genus Brucella and Mycobacterium, respectively, which pose significant hazards to both animal husbandry and human health. Currently, mixed infections of these two pathogens are prevalent in livestock production; thus, establishing a molecular diagnostic method for the simultaneous detection and analysis of brucellosis and tuberculosis is crucial for the prevention and control of these diseases. By utilizing conserved regions within the genomes of Brucella and Mycobacterium, we designed specific primers and probes. After optimizing the developed qPCR assay conditions, we determined the lower limit of detection to be ten copies/ μL. Cross-testing with other bovine-derived pathogens demonstrated no cross-reactivity. Repeatability tests indicated that the coefficient of variation for the developed qPCR assay was less than 4.10% both within and between batches. We employed both the developed qPCR assay and a commercial qPCR assay to analyze sixty mixed infection samples of Brucella and Mycobacterium from various regions. The results revealed positivity rates of 100% and 96.67% for Brucella, and 100% and 95.00% for Mycobacterium, respectively. These findings indicate that a highly sensitive, specific, reproducible, and versatile qPCR method has been developed for the simultaneous quantitative detection of Brucella and Mycobacterium, which can be applied in studying the pathogenesis and epidemiology of these pathogens.